The girl games - Holub, Joan (Holub, Joan. Goddess girls ;, 2012)
" Artemis, Persephone, Aphrodite, and Athena are sick and tired of being left out of the annual boys-only Olympic Games. Their solution? The Girl Games! But as the Goddess Girls work to make their dream into a reality, they come up against plenty of chaos and competition. Told in alternating points of view, this super special is packed with Olympic spirit!"--Publisher's website.